2017
DOI: 10.1016/j.ijscr.2017.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive gastrointestinal food allergy in neonates and its possible relationship to necrotizing enterocolitis

Abstract: HighlightsFood allergy in neonates with secondary necrotizing enterocolitis is extremely rare.No typical risk factor for necrotizing enterocolitis due to food allergy was found.Methicillin-resistant Staphylococcus aureus in the stool may be a risk factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Staphylococcus aureus is associated with the onset of FA. 38 Staphylococcus causes intestinal infection and damages intestinal epithelial cells. 39 Compared with healthy infants, FA infants showed a higher abundance of Escherichia-Shigella.…”
Section: Food and Function Papermentioning
confidence: 99%
“…Staphylococcus aureus is associated with the onset of FA. 38 Staphylococcus causes intestinal infection and damages intestinal epithelial cells. 39 Compared with healthy infants, FA infants showed a higher abundance of Escherichia-Shigella.…”
Section: Food and Function Papermentioning
confidence: 99%
“…Suda et al . 17 reported that some cases of sFA subsequently developed into NEC. They suggested that a persistent decrease in the platelet count may indicate this tendency.…”
Section: Discussionmentioning
confidence: 99%
“…Suda et al . 17 reported that 2 neonates with sFA required laparotomy due to secondary NEC. Intestinal edema and injury would be induced when proper avoidance of suspected-food is not practiced, and severe intestinal inflammation might progress to local necrosis and perforation or endogenous infection, mimicking NEC and causing enteral complications such as intestinal stricture and other acquired SAGT.…”
Section: Discussionmentioning
confidence: 99%